Uji Lapang Vaksin Mycoli Untuk Pencegahan CRD Pada Ayam Potong = Field Trial of Mycoli Vaccine for CRD Protection in Broiler Chickens. - Soeripto .; Andriani . (Jurnal Sain Veteriner, 2006)
Field trial of Mycoli vaccine was carried out on a commercial broiler farm in West Java, Indonesia. The number of vaccinated chickens was 3.000 heads and another 3.000 heads were used as control. The route of vaccination was done via subcutaneous tissue behind the head with a dose of 0.2 mIthead. The vaccination was given at 4 days of age concurrently with ND vaccine adminitration. As a field control, a number of 50 vaccinated chickens designated as Group I and another 50 non vaccinated chickens designated as Group II taken from the field trial were kept in Balitvet pens. Each of the Group was then divided again into 10 subgroups of 5 heads, kept in wire cages. At 4 weeks of age, chickens in 5 subgroups of Group I and of Group II were challenged with wild strain of Mycoplasma gallisepticum (MG) R980 via abdominal airsacs. Blood samples were collected from all chickens before challenged and before termination day for serology MG antibody. Feed and body weight gain were measured every week. All simulated chickens at Balitvet were killed at 42 days of age and examined for pathological lesions. The results of field trial showed that vaccinated chickens had produced body weight gain of 510g and feed conversion of 0.04 per head better than non-vaccinated groups, but statistically no difference between vaccinated and control chickens. The simulated chickens at Balitvet showed that chickens of Group I had shown better protection against MG challenge than chickens of Group H. The vaccinated chickens produced body weight gain of 39g and rate of feed conversion of 0.35 per head better than control chickens, and the vaccinated challenged chickens had body weight gain and feed conversion of 48g and 0.34, respectively better than the control challenged chickens.